Self-reported Difficulties in Learning English as a Second Language for Third-age Students in Poland - Matusz, Łukasz; Rakowska, Anna Maria (Theory and Practice of Second Language Acquisition, 2019)
The problem of teaching English to third-age students is among the issues in ELT which have gained increasing attention and interest in recent years. The aim of this paper is to identify difficulties in learning English as a foreign language reported by students taking part in language courses at third-age universities in Poland. The research is based on the questionnaire distributed among the group of 70 third-age students of English. The results show that the problems the learners report are cantered around their age- and health- related conditions, as well as their general attitudes concerning foreign language learning. It is hoped that the present study will constitute a minor contribution to the study of learning needs and expectations of senior students in Poland.